2023
DOI: 10.20944/preprints202305.2272.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Hypocholesterolemic Potential of the Edible Algae Fucus Vesiculosus: Proteomic and Quantitative PCR Analysis

Abstract: A brown seaweed consumed worldwide, Fucus vesiculosus, has been used to prevent atherosclerosis and hypercholesterolemia, among other uses, however, the mechanisms of action that lead to these effects are not yet fully understood. An F. vesiculosus aqueous extract, prepared as a soup was characterized as rich in sev-eral bioactive compounds, mainly phlorotannin and peptides. This work aims to study the in vitro effect of this extract on the expression of different proteins involved in the synthesis and transpo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, the compounds in the extracts have a promising potential for lowering cholesterol permeation in the intestinal lining, contributing to control of dietary cholesterol absorption. Considering previous results on other brown seaweeds, such as Fucus vesiculosos [ 47 ], and the composition of Aramé and Nori extract [ 25 ], it can be suggested that the extract compounds could interfere with the expression of cholesterol transporters in the intestinal lining NPC1L1 and ABC transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the compounds in the extracts have a promising potential for lowering cholesterol permeation in the intestinal lining, contributing to control of dietary cholesterol absorption. Considering previous results on other brown seaweeds, such as Fucus vesiculosos [ 47 ], and the composition of Aramé and Nori extract [ 25 ], it can be suggested that the extract compounds could interfere with the expression of cholesterol transporters in the intestinal lining NPC1L1 and ABC transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the compounds in the extracts have a promising potential for lowering cholesterol permeation in the intestinal lining, contributing to control of dietary cholesterol absorption. Considering previous results on other brown seaweeds, such as Fucus vesiculosos [47], and the composition of Aramé and Nori extract [25], it can be suggested that the extract compounds could interfere with the expression of cholesterol transporters in the intestinal lining NPC1L1 and ABC transporters. This is the first report demonstrating Nori extract's ability to inhibit cholesterol permeation in Caco-2 cells, a model of the intestinal lining.…”
Section: Seaweed Extract Permeation In Vitro Through Human Caco-2 Cellsmentioning
confidence: 90%